Prescribing pattern of antidiabetic drugs in tertiary care hospital - Kumar, Pothuru Anil; Kumar, RajKeelu Raj (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The aim of the current study was to investigate the prescribing pattern of anti-diabetic drugs in diabetic patients attending tertiary care teaching hospital in Kurnool. Methods: A prospective, cross-sectional, observational survey was carried out in 100 patients of diabetes mellitus attending diabetes outpatient/medicine outpatient departments, to assess their prescribing pattern of anti-diabetic drugs. Results: Average number of anti-diabetic drugs per prescription was 1.4. Metformin (biguanide) was the commonest prescribed individual drug among oral hypoglycemic agents. Fixed dose combination of biguanide and sulfonylurea was prescribed commonly. Monotherapy dominated over polytherapy and there was a higher percentage of use of insulin in type 2 diabetics. Conclusions: OHAs still dominate the prescribing pattern, but there was a shifting trend toward the use of insulin preparations in the management of type 2 diabetes mellitus. Intensification of current drug treatment as well as planning multiple drug interventions with lifestyle modification is necessary.